Practical aspects of the diagnosis and management of pyoderma gangrenosum - Chen, Bo; Li, Wei; Qu, Bin (Frontiers in Medicine, 2023)
Pyoderma gangrenosum (PG) is a rare autoinflammatory ulcerative neutrophilic skin disease. Its clinical presentation is a rapidly progressing painful skin ulcer with ill-defined borders and surrounding erythema. The pathogenesis of PG is complex and not fully understood. Clinically, patients with PG often have various systemic diseases, the most common being inflammatory bowel disease (IBD) and arthritis. Due to the lack of specific biological markers, diagnosing PG remains difficult, which easily resulting in misdiagnosis. Some validated diagnostic criteria have been applied in clinical practice that facilitate its diagnosis. The treatment of PG currently consists mainly of immunosuppressive and immunomodulatory agents, especially biological agents, which have bright prospects for PG therapy. After the systemic inflammatory response is controlled, the problem of wounds becomes the main contradiction in PG treatment. Surgery is not controversial for PG, increasing evidence shows that with adequate systemic treatment, the benefits of reconstructive surgery for patients are increasing.